KEPEMIMPINAN KEPALA SEKOLAH DALAM PEMBERDAYAAN GURU DI SEKOLAH DASAR NEGERI 15 SENUTUL KECAMATAN ENTIKONG - Poniman, Yohanes (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe ability of the principal in leadership can affect teacher empowerment. The focus of this research is to know the principal's leadership in the effort of teacher empowerment. This research uses descriptive Â method with qualitative research type. This research uses qualitative method with descriptive approach type. The location of research at the State Elementary School 15 Senutul. Subject research subjects, teachers and committees. The data collection procedure uses observation, interview and documentation. Model of Miles and Haberman's data analysis techniques by data reduction, data presentation and conclusion. The results show that Leadership increases the potential of human resources through empowerment, guidance, improvement of professional duties, coordination and discipline. Internal support factors are strong coordination, tasks and responsibilities that are oriented towards school interests and needs. While the inhibiting factors are funds, facilities, and barriers are: road infrastructure and limited access to communications. Actualization of empowerment through the development of teacher teacher potentials develops curriculum, guides students, professional development through teacher work groups, training, seminars and workshops. Aspects of leadership are implemented effectively, evidenced by the large attention and responsibility of principals to exploit the potential that exists through the improvement of teacher actualization.Keywords: Leadership, Teacher Empowerment